The Future of Urban Design: Opportunities of a New Pragmatism and the Disappearance of the Client-Expert - Firley, Eric (ARCC Conference Repository, 2014)
In a similar way as for architecture, the client demands for urban design have considerably changed over the last two decades. Since its official founding in the post-war era practiced as a form oriented design discipline that focused on the medium scale somewhere in between architecture and regional planning, it is now understood as an evidence-based management discipline that steers a gradual process of change and adaptation. This paper elaborates on the thesis that visibility in terms of traceability and accountability will become an increasingly important feature for the profession. The point is made that the urban designer has to convey and prove his knowledge to a decision-taking client that does not necessarily have the technical competence to decide, nor a clear program to follow. Functional considerations and their fulfillment are still key, but are complemented by far more strategic demands that have grown in relevance through the recent emphasis on the urban condition as a main driver of economic competitive capacity.It should be clarified that the author, due to his origin and research experience, often uses European references and that he focuses on an analysis of the profession in the developed rather than developing world. The content of this paper is predominantly based on the knowledge gathered during the writing of three comparative books about housing typologies, high-rise in the urban context and planning methodologies. This knowledge has been applied to the professional sector following a research consultancy mission in a campus planning agency during the summer of 2012.